Synergistically improved cardiovascular outcomes in type 2 diabetes mellitus patients with combined treatment of SGLT-2 inhibitors and pioglitazone - Li, Yan-Rong; Wang, Chih-Ching; Liu, Chi-Hung; Yen, Chieh-Li; Wu, Victor Chien-Chia; Huang, Evelyn Jou-Chen; Lee, Ching-Yu; Hsiao, Ching-Chung (Frontiers in Endocrinology, 2024)
Sodium-glucose co-transporter-2 inhibitors (SGLT2i) have cardiovascular (CV) benefits, particularly in reducing the risk of heart failure (HF). Pioglitazone (Pio) has shown potential in decreasing the risks of recurrent stroke, non-fatal myocardial infarction (MI), and all-cause mortality but increasing risks of HF. Our study aimed to examine the synergistic effects on CV outcomes in patients with type 2 diabetes mellitus (T2DM) who received the combined treatment of SGLT2i and Pio.A total of 117,850 patients with T2DM and without a history of HF were selected as the observational study cohort from the Chang Gung Research Database (CGRD) in Taiwan between January 1, 2016, and December 31, 2019. The primary composite outcome was 4-point major adverse CV events (4P-MACE), including CV death, non-fatal MI, non-fatal ischemic stroke, and hospitalization for HF. The study was divided into four groups: a combined treatment group in which SGLT2i and Pio were used, two individual groups in which SGLT2i or Pio was used separately, and a reference group (non-study drugs).Combined treatment of SGLT2i and Pio had the lowest risk of 4P-MACE (adjusted hazard ratio [aHR], 0.66; 95% confidence interval [CI], 0.54-0.80) compared with the reference group after a mean follow-up of 2.2 years. There was no significant difference in risks of hospitalization for HF (adjusted subdistribution hazard ratio, 0.73; 95% CI, 0.49-1.07) compared with the reference group.In T2DM patients without HF, the combined treatment with SGLT2i and Pio may synergistically provide CV benefits without increasing risks of HF.